Role dimensions of general practice nurses in Ireland - Mary Casey; Laserina O' Connor; Walter Cullen; Áine Carroll (James Cook University, 2023)
Introduction: Primary care has the potential to address the challenges associated with the rise of chronic conditions and an aging population; however, General Practitioners are increasingly struggling to meet these demands. Fundamental to the provision of high-quality primary care is the role of the general practice nurse, who typically provides a wide range of services. Examining the current role of general practice nurses must be a first step to determining their educational needs for enhancing their long-term future contribution to primary care.Method: A survey design was used to explore the role of general practice nurses. A purposeful sample of general practice nurses (n=40) was undertaken between April and June 2019. Data were analysed using the Statistical Package for Social Science (SPSS V 25.0. Armonk, NY: IBM).Results: General practice nurses appear to have an agenda in relation to activities associated with wound care, immunizations, and respiratory and cardiovascular issues. Challenges to future enhancement of the role were associated with undertaking further training and their experience of having more work transferred to general practice without concomitant reallocation of resources.Discussion: General practice nurses have extensive clinical experience to deliver major improvements in primary care. Educational opportunities need to be provided for upskilling existing general practice nurses and to attract future nurses into this important area. Greater understanding of the role and the potential contribution of the role in general practice is required among medical colleagues and the public.